Oh, musica! - Aliki ([Barcelona] : Editorial Juventud, 2004)
Surveys the history and components of music, concentrating on Western musical traditions.
Translation of: Ah, music!
Accelerated Reader AR-ATOS
Accelerated Reader AR
Text in Spanish.
Keywords: Music -- History and criticism -- Juvenile literature; Music appreciation -- Juvenile literature; Spanish language materials